Measurement of equilibrium potential of Cl2/Cl− redox couple in molten chlorides - Zujian Tang; Qilin Yuan; Shangping Zhu; Osamu Takeda; Hongmin Zhu (Electrochemistry Communications)
The current interruption method is used to determine the equilibrium potential of the Cl2/Cl− redox couple, and the theory behind the measurement is discussed. Different AgCl/Ag reference electrodes are prepared and calibrated by measuring the equilibrium potential of Cl2/Cl− redox couple. Cyclic voltammograms against the different AgCl/Ag reference electrodes before and after calibration in pure lithium chloride are reported, showing good agreement with thermodynamic calculations.